MANAGING STRATEGIC RESOURCE INTERDEPENDENCE FOR COASTAL DISASTER MITIGATION: A COLLABORATIVE GOVERNANCE STUDY IN PALU - Suasa Suasa; Muhammad Rapi; Asrifai A. Arabe; Mukarramah Mukarramah; Meldi Amijaya (Natapraja, 2026)
This study examines how interdependence among actors shapes coastal disaster mitigation governance in Palu City following the 2018 disaster. In recent studies, there are still gaps in understanding how power relations, resource distribution, and legitimacy influence mitigation effectiveness in a multi-actor context. To address this, this study uses a qualitative approach with an intrinsic case study design and a Resource Dependence Theory (RDT) framework. Data were collected through in-depth interviews, field observations, and document analysis, then analysed using qualitative social network mapping with coding based on four RDT dimensions: organisational strategy, programs, resources, and institutions. The findings indicate that mitigation governance in Palu is defined by asymmetric interdependence patterns, where actors with control over resources, particularly financial and technical resources, tend to dominate the policy agenda. However, this interdependence also opens up space for strategic collaboration through mechanisms for the exchange of legitimacy, knowledge, and capacity. Based on these findings, this study proposes the concept of “strategic interdependence for resilience,” which repositions interdependence as an active and institutionalized governance instrument. This study contributes by extending RDT into the context of coastal disaster governance and offers an analytical framework for understanding the transformation of dependency into adaptive capacity in complex socio-ecological systems.